ANALISIS PASANGAN SUAMI ISTRI YANG TIDAK MEMPUNYAI ANAK DALAM MEMPERTAHANKAN PERKAWINAN - Iwan Yuda Wibawa; Nuraini Asriati; Iwan Ramadhan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine (1) Efforts to understand each other husband and wife whodo not have children in maintaining a marriage. (2) Efforts to respect each other'shusband and wife who do not have children in maintaining the marriage. (3) Efforts tounderstand each other's husband and wife who do not have children in maintaining theirmarriage by being honest with each other, respecting differences and giving a gift tocouples in the absence of children in the family so that their family is maintained. Themethod used in this study is in the form of a narrative in the data collection process. Thesources of data in this study are married couples who do not have children in maintainingtheir marriage. The data in this study are the results of interviews with married coupleswho do not have children in maintaining their marriage. For the process of collectingdata, namely the observation and interview techniques in this study. Data collection toolsused observation guides, interview guides and notebooks and archives. The results of thestudy show that married couples who do not have children in maintaining their marriageevery marriage must experience problems in the household, one of which is the absenceof a child in their marriage, surely the couple feels anxiety in the household, thingshusband and wife strive for so that their relationship remains harmonious with mutualhonest efforts, respecting differences and efforts to please each other, for example,honestly, a husband compliments his wife's cooking, respects each other's differences byfollowing the partner's will to be unselfish and prioritizes mutual interests and efforts tomake couples feel happy, namely giving gifts to their partners.Keywords: Husband, maintain marriage, wife